HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN 3M (MEMAKAI MASKER, MENCUCI TANGAN DAN MENJAGA JARAK) SELAMA PANDEMI COVID-19 PADA LANSIA DI WILAYAH KERJA UPTD PUSKESMAS TALUN -KABUPATEN CIREBON - Yani Kamasturyani; Rosalia (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
In optimizing the quality of life of the elderly during the Covid-19 pandemic, therole and support of family and community is very much needed. This study aimsto determine the relationship between family support and 3M compliance(wearing masks, washing hands, and maintaining distance) during the COVID19 pandemic in the elderly in the UPTD work area of the Talun Health Center,Cirebon Regency. This research method uses an analytical survey with a crosssectional approach. The population is the elderly in the working area of UPTDPuskesmas Talun, Cirebon Regency and the number of samples is 94 people. Thesampling technique used was purposive sampling. Sampling technique with certain considerations. Data analysis used the Chi-Square test with asignificance value of = 0.10. The results of univariate analysis showed that mostof the respondents (75.5%) received family support in the high category. Thenmost of the respondents (76.6%) are included in the 3M compliance category.Bivariate analysis with Chi-Square test shows p-value 0.001 < 0.10, so H0 isrejected, meaning that there is a relationship between family support and 3Mcompliance (wearing masks, washing hands, and keeping a distance) during thecovid 19 pandemic in the elderly in the UPTD Puskesmas Talun work area.Cirebon Regency. In future research, it is hoped that it will focus more on theapplication of health promotion related to family support